Effect of covering materials on off-season cut flower production in chrysanthemum (Dendrathema grandiflora) - SANGMA, PALMSEY M; DHIMAN, SITA RAM; THAKUR, PRIYANKA; GUPTA, Y C (The Indian Journal of Agricultural Sciences, 2016)
Studies on the effect of covering material on off-season cut flower production of chrysanthemum (Dendranthema grandiflora Tzvelev) were carried out at the experimental farm of the Department of Floriculture and Landscape Architecture, Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, during 2011 in naturally ventilated polyhouse. The experiment was carried out using three types of covering materials(viz. tarpaulin, high density polyethylene (HDPE) and black sateen cloth) and four cultivars each of standard (Purnima, Yellow Star, Tata Century and White Star) and spray (Ajay, Birbal, Nanako and White Bouquet) varieties. Findings revealed that HDPE was the best alternative covering material to tarpaulin as optimum plant height (83.33 cm), plant spread (40.54 cm), maximum number of cut stems (4.21), duration of flowering (33.54 days) and earliest flower bud formation (91.07 days) and flowering were obtained in plants under HDPE. Flowering was earlier under controlled photoperiod than natural photoperiod. Peak flowering was earliest (140.36 days) in plants under HDPE* cover as compared to plants under natural photoperiodic conditions which took maximum number of days (176.19), to come to peak flowering. The varieties were assigned to different response group under controlled photoperiodic conditions with HDPE. All the varieties tested were found suitable for off-season flower production.